A Systematic Methodology for Multi-Images Encryption and Decryption Based on Single Chaotic System and FPGA Embedded Implementation. (24th June 2014) - Zheng, Hanzhong; Yu, Simin; Xu, Xiangqian
Abstract : A systematic methodology is developed for multi-images encryption and decryption and field programmable gate array (FPGA) embedded implementation by using single discrete time chaotic system. To overcome the traditional limitations that a chaotic system can only encrypt or decrypt one image, this paper initiates a new approach to design n -dimensional ( n -D) discrete time chaotic controlled systems via some variables anticontrol, which can achieve multipath drive-response synchronization. To that end, the designed n -dimensional discrete time chaotic controlled systems are used for multi-images encryption and decryption. A generalized design principle and the corresponding implementation steps are also given. Based on the FPGA embedded hardware system working platform with XUP Virtex-II type, a chaotic secure communication system for three digital color images encryption and decryption by using a 7D discrete time chaotic system is designed, and the related system design and hardware implementation results are demonstrated, with the related mathematical problems analyzed.